2007
DOI: 10.1016/j.cub.2007.01.047
|View full text |Cite
|
Sign up to set email alerts
|

Interphase Microtubules Determine the Initial Alignment of the Mitotic Spindle

Abstract: In the fission yeast Schizosaccharomyces pombe, interphase microtubules (MTs) position the nucleus [1, 2], which in turn positions the cell-division plane [1, 3]. It is unclear how the spindle orients, with respect to the predetermined division plane, to ensure that the chromosomes are segregated across this plane. It has been proposed that, during prometaphase, the astral MT interaction with the cell cortex aligns the spindle with the cell axis [4] and also participates in a spindle orientation checkpoint (SO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 27 publications
3
32
0
Order By: Relevance
“…1A). Consistent with previous reports (Gachet et al, 2001;Gachet et al, 2004;Tournier et al, 2004;Vogel et al, 2007) essentially all wild-type cells initiated SPB separation within 30 degrees of the long axis of the cell ( fission yeast cells have a mechanism to align the spindle with the global axis of polarity.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…1A). Consistent with previous reports (Gachet et al, 2001;Gachet et al, 2004;Tournier et al, 2004;Vogel et al, 2007) essentially all wild-type cells initiated SPB separation within 30 degrees of the long axis of the cell ( fission yeast cells have a mechanism to align the spindle with the global axis of polarity.…”
Section: Resultssupporting
confidence: 92%
“…MT bundles in these cells are very often misaligned with respect to the long axis (Carazo-Salas and Nurse, 2006;Daga et al, 2006a) and are found to have similar misalignment of the mitotic spindle. Similar results were also found in cells lacking the S. pombe EB1 homologue Mal3, which also displays short MTs (Vogel et al, 2007).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…As a consequence, 30% of ⌬mto1 cells lack cytoplasmic microtubules and the remainder possess a single interphase microtubule bundle. In fission yeast, cytoplasmic microtubules are required for positioning the nucleus in the centre of the cell and for the initial alignment of the mitotic spindle along the longitudinal axis of the cell (Tran et al, 2001;Vogel et al, 2007). To assess the effect of interphase microtubules on Rabl formation, we monitored spindle pole and kinetochore position in ⌬mto1 ndc80-gfp cdc11-cfp cells.…”
Section: Resultsmentioning
confidence: 99%